REGIONAL FEATURES OF THE STRUCTURE AND DETECTABILITY OF PRIMARY OCCUPATIONAL MORBIDITY IN THE NOVOSIBIRSK REGION FOR THE PERIOD FROM 2019 TO 2023 - Радоуцкая, Елена Юрьевна; Онищук, Ярослава Игоревна; Свечкарь, Полина Евгеньевна; Шмыгун, Маргарита Владимировна (Medicine in Kuzbass, 2025)
The study found that among patients with a newly diagnosed occupational disease, workers of industrial enterprises in the Novosibirsk Region predominate. The structure of the diseased is overwhelmingly male, consistently accounting for more than 70% of all registered first cases of occupational diseases and the individuals diagnosed with them. The reasons complicating the primary examination of the connection between a disease and profession, as well as the format of documents submitted for examination, were analyzed. The referral pathways for the examination of the connection between a disease and profession were reviewed. The structure of primary occupational morbidity was studied.
Keywords: examination of the connection between a disease and profession; periodic medical examinations; sanitary-hygienic characteristics of working conditions; special assessment of working conditions